2017
DOI: 10.3892/etm.2017.5204
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of hypertensive disorders in pregnancy with procedures of in vitro fertilization and pregnancy outcomes

Abstract: We investigated the correlation of hypertensive disorders in pregnancy with different procedures of in vitro fertilization, and analyzed pregnancy outcomes of patients with hypertensive disorders in pregnancy. A retrospective analysis was performed on the medical records of 658 maternity patients who conceived through in vitro fertilization in Maternal and Child Health Hospital of Wuxi. Patients were divided into two groups according to different fertilization procedures: i) the routine in vitro fertilization-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
(22 reference statements)
0
10
0
1
Order By: Relevance
“…Therefore, the existing literature and research concluded that the early, middle and late stages of placental development exhibit distinct differences in physiological functions and gene expression, and understanding the effects of pathogenic factors on early placental development, function and gene expression contributes to early diagnosis and medical intervention (34). a growing body of evidence supports the hypothesis that various adverse pregnancy outcomes observed after arT originate from suboptimal placentation caused by abnormal trophoblast function (2,3). in humans, after adjusting for several confounding factors, the risk of spontaneous abortion is higher in arT cohorts than for spontaneous pregnancies (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the existing literature and research concluded that the early, middle and late stages of placental development exhibit distinct differences in physiological functions and gene expression, and understanding the effects of pathogenic factors on early placental development, function and gene expression contributes to early diagnosis and medical intervention (34). a growing body of evidence supports the hypothesis that various adverse pregnancy outcomes observed after arT originate from suboptimal placentation caused by abnormal trophoblast function (2,3). in humans, after adjusting for several confounding factors, the risk of spontaneous abortion is higher in arT cohorts than for spontaneous pregnancies (35).…”
Section: Discussionmentioning
confidence: 99%
“…There is currently growing interest in the potential risks associated with assisted reproductive technology (arT). after adjusting for several confounding factors, the risk of numerous adverse outcomes during the perinatal period, including miscarriage, premature birth, low birth weight, intra-uterine growth retardation and gestational hypertension, are higher in in vitro fertilization and embryo transfer (iVF-eT) cohorts than for spontaneous pregnancies (1)(2)(3). over the last few years, the early stages of mammalian embryonic development have been shown to be very sensitive to the microenvironment, with long term effects on fetal, postnatal and adult health (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…In common with singleton pregnancies, twin pregnancies complicated by PE are at greater risk of an adverse pregnancy outcome 43 .In contrast with our findings, some studies suggest that IVF is significantly associated with a higher incidence of PE. Also,severe PE was more prevalent in the singleton IVF-PE group than in the singleton SC-PE group [44][45][46] .…”
Section: Discussionmentioning
confidence: 91%
“…In a study by Xiong et al, in 2017, the authors stated that the risk of gestational hypertension in pregnancy has a certain correlation with the ICSI fertilization technology [ 20 ]. In addition, many studies supported in their results that ART pregnancy has been reported as a factor linked to an increased risk for hypertension [ [21] , [22] , [23] , [24] ].…”
Section: Discussionmentioning
confidence: 99%